Di-μ-chlorido-bis{(μ-1,8-bis(diisopropylphosphanyl)-9,10-dihydro-9,10-ethanoanthracene-κ2P:P′)-μ-chlorido-μ-methylidene-dipalladium(II)} tetrahydrofuran pentasolvate - Schnetz, Thomas; Rominger, Frank; Hofmann, Peter (Acta crystallographica. Section E, Structure reports online, 2010)
The title compound, [Pd4(CH2)2Cl4(C28H40P2)2]·5C4H8O, possesses a tetranuclear palladium core with four bridging chlorido ligands and two bridging methylene units, as well as two bridging anthracene-based bis-phosphine ligands. This tetranuclear complex can be considered as being composed of two μ-chlorido-bridged LPd2 units. The structural motif of these LPd2 units shows two doubly bridged palladium centers between the P atoms of the bis-phosphine ligand. One of these bridges is a μ-Cl atom, the other a μ-methylene group. The coordination environment around each palladium center is essentially square planar. We ascribe the oxidation state +II to the palladium centers and do not assume Pd—Pd bonds [shortest distances 2.8110 (5) and 2.8109 (6) Å]. Co-crystallized with the palladium complex we found five non-coordinating tetrahydrofuran solvent molecules, one of which is disordered over two positions in a 0.429 (9):0.571 (8) ratio.
Der Ausdruck μ-1,8-bis(diisopropylphosphanyl)-9,10-dihydro-9,10-ethanoanthracene-κ2P:P′ erscheint im Titel in eckigen Klammern
Das PDF enthält zusätzlich einen Anhang von 21 Seiten
Gesehen am 27.06.2023